Modern weapons and military equipment for issue 4/2013 - Ostojić, Nikola M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Russian exoskeleton "Egzoatlet" U.S. Army offered a self-propelled robot - a machine gun Newspapers in urban warfare Haris "screened tablet" "Prism" and the American concept of cyber warfare